Effects of acute exposure to ultra-wideband pulsed electromagnetic fields on the liver and kidneys of mice. (2nd April 2020) - Guo, Kaihong; Zhang, Yali; Fang, Xinlei; Fan, Peiyao; Shang, Sen; Fan, Fan; Wu, Hongyan; Man, Menghua; Xie, Yanzhao; Lu, Xiaoyun
ABSTRACT: The biosafety of ultra-wideband (UWB) pulses, which are characterized by simultaneously high power and a high bandwidth ratio, has gained increasing attention. Although there is substantial prior literature on the biological effects of UWB pulses on both cells and animals, an explicit, unequivocal and definite pattern of the corresponding biological responses remains elusive, and the systemic secondary consequences are also still not fully understood. In this study, we found that exposing mice to UWB pulses resulted in the alteration of several biochemical blood parameters, which further prompted us to investigate changes in the liver and kidneys of mice exposed to UWB pulses with different field intensities and different durations. The data demonstrated that exposure to UWB pulses significantly increased the levels of ALT and AST, increased oxidative stress, and could even induce the accumulation of lipid droplets in hepatocytes. The total number of pulses under the tested acute exposure regiment contributed most to the observed hepatic and rental dysfunction. Notably, the physiological and molecular changes recovered approximately 72 hours after exposure. These results imply the potential risk of acute exposure to UWB pulses, and highlight the meaningful targets for further long-term study of chronic exposure.